2018
DOI: 10.1093/jisesa/iey057
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Phylogenetic Analysis of Basic Helix-Loop-Helix Genes in the Diamondback Moth

Abstract: Basic helix-loop-helix (bHLH) transcription factors play essential roles in regulating eukaryotic developmental and physiological processes such as neuron generation, myocyte formation, intestinal tissue development, and response to environmental stress. In this study, the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), genome was found to encode 52 bHLH genes. All 52 P. xylostella bHLH (PxbHLH) genes were classified into correspondent bHLH families according to their orthology with bHLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Similar to D. melanogaster and T. castaneum (Moore et al, 2000;Bitra et al, 2009;Zeng et al, 2018), only 1 AP4 gene and 1 ARNT gene were identified in A. mellifera in our study. P. xylostella contains 52 bHLH genes in 38 families, but lacks AP4 and SREBP genes (Zeng et al, 2018). We identified 56 bHLH genes, including 1 AP4, 1 SREBP, 1 Lep, 1 more Clock, 2 more H/E(spl), and 2 instead of 4 SCL genes in P. xylostella, based on the latest genome annotation (Table S2).…”
Section: Comparison and Phylogenetic Analysis Of Bhlh Members In 5 In...supporting
confidence: 58%
See 4 more Smart Citations
“…Similar to D. melanogaster and T. castaneum (Moore et al, 2000;Bitra et al, 2009;Zeng et al, 2018), only 1 AP4 gene and 1 ARNT gene were identified in A. mellifera in our study. P. xylostella contains 52 bHLH genes in 38 families, but lacks AP4 and SREBP genes (Zeng et al, 2018). We identified 56 bHLH genes, including 1 AP4, 1 SREBP, 1 Lep, 1 more Clock, 2 more H/E(spl), and 2 instead of 4 SCL genes in P. xylostella, based on the latest genome annotation (Table S2).…”
Section: Comparison and Phylogenetic Analysis Of Bhlh Members In 5 In...supporting
confidence: 58%
“…1). Previous studies also showed that the grouping of bHLH domains of P. xylostella does not follow strict criteria (Wang et al ., 2007; Zeng et al ., 2018). SlbHLHs in groups A, B, and D contain only the bHLH domain, except SlTai.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations